Analisis Aspek Sosiologis dalam Novel Corona Karya Sdavincii - Anggarani, Ni Nyoman Novita; Nama, I Ketut; Jumadiah, Sri (Stilistika : Journal of Indonesian Language and Literature; Vol 2 No 2 (2023): Volume 2 No 2, April 2023, 2023)
This research aims to describe (1) the structure that built Sdavincii's novel Corona; and (2) sociological aspects contained in Sdavincii’s novel Corona. The theories used in this study are the structural theory of Nurgiyantoro and the literary sociology of Sapardi Djoko Damono. The method used to collect data is a library study method with advanced techniques in the form of reading, listening, and recording techniques. Then to analyze the data used analytical descriptive methods are done by taking problems or focusing on problems as they were when the research was done. The results of this study showed that the intrinsic elements analyzed in Sdavincii’s novel Corona include: characterization, plot and setting. The political aspect contained in Corona novel, is the problem of political conspiracy. The health aspect is about corona. The economic aspect reveals the economic differences between Aragon and the Catalans. The moral aspect addresses moral issue of good morals. The family aspect talks about the Lago family and Ella's family and the true relationship between Lago and Ella.